Implementation of Segmentation, Targeting, and Positioning (STP) Marketing Strategy to Increase Sales Volume at Rebon Shrimp Paste Producers in Probolinggo - Ahmad Hidayatullah; Muhamad Naely Azhad; Pawestri Winahyu (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
The purpose of this study is to determine the formulation of strategies used in increasing sales of shrimp paste products in Mayangan Village, Mayangan District, Probolinggo City and to find out the implementation of strategies used in increasing sales of shrimp paste products in Mayangan Village, Mayangan District, Probolinggo City. The method used in this study is qualitative research method. In a qualitative approach to obtain information by in-depth interviews with informants as well as document review and observation to assess the target market (targeting) and product positioning (positioning). The results showed that with a directed marketing strategy can help a business activity or company in delivering its products to consumers in accordance with the wants and needs of each consumer. One strategy that is often used by business activists is the segmentation, targeting, and positioning method. Where this strategy itself has also been applied in the sale of rebon paste which is the starting point before doing the marketing mix.